Can information about energy costs affect consumers choices? Evidence from a field experiment - Annina Angelina Boogen; Claudio Daminato; Massimo Filippini; Adrian Obrist (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
There is an ongoing debate in the literature about whether consumers are fully informed when investing in energy efficiency. We experimentally evaluate the role of imperfect information or limited attention about energy costs of home appliances and light bulbs on households' choices. Using in-home visits, we collect information on the energy efficiency of home appliances and light bulbs that households own. Exploiting these unique data, the intervention provided treated households with customized information about the potential of monetary savings from the adoption of new comparable efficient durables. We find a substantial impact of our information treatment on both the energy efficiency of the newly purchased durables and the intensity of utilization of existing home appliances. Our findings suggest that individuals are not fully informed about or pay attention to energy costs when purchasing and utilizing home appliances.
Keywords: C93; D12; D83; Q40; 330; Imperfect information; Limited attention; Consumers durable choices; Energy efficiency; Field experiment